2015
DOI: 10.1007/s00894-015-2743-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of donor strength of extended alkyl auxiliary groups on optoelectronic and charge transport properties of novel naphtha[2,1-b:6,5-b′]difuran derivatives: simple yet effective strategy

Abstract: The present study spotlights the designing of new derivatives of 2,7-bis (4-octylphenyl) naphtho [2,1-b:6,5-b'] difuran (C8-DPNDF) by substituting the alkyl groups (methyl, ethyl, propyl, butyl, pentyl, hexyl, and heptyl groups) at para position. Density functional theory (DFT) and time-dependent density functional theory (TD-DFT) methods are employed to optimize the molecular structures in ground and first excited states, respectively. Several electro-optical properties including hole/electron reorganization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Molecular geometries were optimized using DMol 3 module with GGA/PBE function [39][40] and the ESP charges were embedded to target structure. Crystal structures were predicted under Dreiding force field [41] and restricted to the seven most popular space groups [42] (P21/c, P-1, P212121, P21, C2/c, PBCA, and P1). Previous research shown that the crystal with larger crystal density and lower energy was more stable [43][44] .…”
Section: Crystal Structure Predictionmentioning
confidence: 99%
“…Molecular geometries were optimized using DMol 3 module with GGA/PBE function [39][40] and the ESP charges were embedded to target structure. Crystal structures were predicted under Dreiding force field [41] and restricted to the seven most popular space groups [42] (P21/c, P-1, P212121, P21, C2/c, PBCA, and P1). Previous research shown that the crystal with larger crystal density and lower energy was more stable [43][44] .…”
Section: Crystal Structure Predictionmentioning
confidence: 99%